(3Yed Gdjhe hGddjdIs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg hdj GdMeO heSJMbg (B... (3aEfj eeJKd eG QSeg SjOfG (B... (3aj ELdGA eNJUQ jTJed Ydi TQM GdEMOi hGdNeSjf QcYI aj GdUdhI aj Gdjhe hGddjdIs
(3BNQgG (B:s
(3BNQgG(B: (3hEf CQGO CHSW aaj cJGH GdfgGjI hEf CQGO GdJaQjY hGdeSGFd GdZGeVI QLY Edi cJGHfG GdeHShW jLOY Pdc eG dG eRjO Ydjg (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 84s
(3GdPQjYI, L (B15: 252s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis